Co-infection prevalence of helminths and associated risk factors among schoolchildren in the Lake Tana Basin, Northwest Ethiopia - Tadesse Hailu; Abolghasem Siyadatpanah; Roghayeh Norouzi (BMC Infectious Diseases)
Abstract Background Helminths are important public health infectious agents and are highly prevalent in the tropics, including Ethiopia. Schoolchildren are highly vulnerable to these parasitic infections due to several personal habits. Although their helminths co-infection prevalence is significant, less attention is given to understand the burden. So far prevention of helminths has been conducted for decades, their co-infections are still a major challenge in endemic areas. Therefore, this study aimed to determine the helminths co-infection prevalence and associated risk factors among schoolchildren in the northwest Ethiopia. Methods School-based cross-sectional study was conducted among 435 schoolchildren in Amhara region in 2019. Risk factors associated with the helminths co-infection identified using structure questionnaire and stool samples were collected for analysis. The stool samples were processed using modified formol ether concentration technique, spontaneous tube sedimentation technique, Baermann concentration technique, agar plate culture and real-time polymerase chain reaction. Data was entered and analyzed using SPSS version 23 statistical software. The prevalence of each helminth species and their co-infections were computed using descriptive statistics. Univariate and multivariate logistic regression were used to determine risk factors associated with helminths co-infection. Variables with p < 0.05 in the multivariate analysis were considered statistically significant. Results The prevalence of helminths and soil-transmitted helminths (STHs) infections was 345 (79.3%) and 289 (66.4%), respectively. The respective prevalence of Strongyloides stercoralis, hookworm, and Schistosoma mansoni were 189 (43.4%), 188 (43.2%), and 121 (27.8%). The prevalence of co-infection was high among S. stercoralis-hookworm co-infections 61 (14.0%) followed by hookworm-S. mansoni 29 (6.7%) co-infections. The prevalence of S. stercoralis-hookworm-S. mansoni triple infection was 27 (6.2%). Improper utilization of latrine (AOR = 2.09; 95%CI:1.07–4.07) and participation in irrigation activities (AOR = 1.96;95%CI:1.17–3.26) were significantly associated with the prevalence of S. stercoralis, hookworm, S. mansoni co-infections. Conclusion The prevalence of helminths co-infections is high in the Lake Tana basin. Improper utilization of latrine and barefoot participation in irrigation activities were the associated risk factors with their co-infections. Hence, proper utilization of latrines and proper implementation of water, sanitation and hygiene, regular shoes wearing, and minimizing fresh water contact should be advocated.